Digital-Based Science Learning Innovation in Improving Generation Z Science Literacy - Dana, Gde Wikan Pradnya (PT. Anagata Sembagi Education, 2025)
This research aims to describe the form of digital-based science learning innovation and analyze its role in improving Generation Z's science literacy. The research method used is descriptive qualitative with data collection techniques through in-depth interviews, observation, and documentation. The research informants consisted of science teachers, generation Z students, and school principals who were purposively selected. The results showed that digital-based science learning innovation was realized through the use of e-learning platforms, virtual simulations, interactive videos, and digital project-based learning. The implementation of this learning is able to improve students' science literacy, especially in terms of concept understanding, critical thinking skills, problem solving, and information literacy. Supporting factors for success include adequate digital infrastructure, teacher readiness, and active student involvement, while barriers include limited facilities, gaps in teacher competence in technology, and potential student distraction when using gadgets. This research confirms that digital-based science learning innovation has a significant contribution in strengthening Generation Z's science literacy in the digital era.